The Relationship between Work Experience, Qualifications, Performance, and Staff Perception of Digital Talent in the Workplace - Irwan Noor; Nur Ambulani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
The biggest challenge in developing digital talent in tertiary institutions is viewing digital reform as a massive entity. Therefore, it is rare to focus on the values of developing digital talent for existing education personnel. Using a growth theory mindset, the research focuses on Working Period, Performance, and Qualification, to see the relationship with Talented education staff. The research uses a sequential explanatory design. The sample consisted of 29 ASNs in one of the faculties of a state university in Indonesia, with random sampling using the online Sample Size Calculator. Questionnaire data were analyzed by SPSS, while interviews with NVivo-12 Pro. The results reveal that both the Working Period, Qualification, and Performance variables correlate with the Talented education of staff. The direction of the relationship also has a positive (+) value. However, qualitative analysis revealed that the activities carried out were more directed at fulfilling the main duties and functions. Behind that, the biggest challenge for them is when dealing with students, who generally come from the digital generation. Therefore, digital reform in higher education also pays attention to developing digital talent for education staff.